2014
DOI: 10.1039/c3pp50374g
|View full text |Cite
|
Sign up to set email alerts
|

Photoswitchable fluorescent diheteroarylethenes: substituent effects on photochromic and solvatochromic properties

Abstract: Photoswitchable fluorescent diheteroarylethenes are promising candidates for applications in superresolution molecular localization fluorescence microscopy thanks to their high quantum yields and fatigue-resistant photoswitching characteristics. We have studied the effect of varying substituents on the photophysical properties of six sulfone derivatives of diheteroarylethenes, which display fluorescence in one (closed form) of two thermally stable photochromic states. Electron-donating substituents displace th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 53 publications
0
49
0
2
Order By: Relevance
“…[23,25] As an alternative, suitable modification of the diarylethene photoswitch itself could give direct access to the envisioned properties. Uno et al [26] und Gillanders et al [27] have reported that the closed form of photochromic diarylethene derivatives bearing sulfone groups can fluoresce, which inspired our research.Here, we present a novel photochromic diarylethene photoswitch for super-resolution microscopy that has a high photostability and strong fluorescence in its closed form. We investigate its photophysical and photochemical properties in solution and in polymers.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…[23,25] As an alternative, suitable modification of the diarylethene photoswitch itself could give direct access to the envisioned properties. Uno et al [26] und Gillanders et al [27] have reported that the closed form of photochromic diarylethene derivatives bearing sulfone groups can fluoresce, which inspired our research.Here, we present a novel photochromic diarylethene photoswitch for super-resolution microscopy that has a high photostability and strong fluorescence in its closed form. We investigate its photophysical and photochemical properties in solution and in polymers.…”
mentioning
confidence: 85%
“…[23,25] As an alternative, suitable modification of the diarylethene photoswitch itself could give direct access to the envisioned properties. Uno et al [26] und Gillanders et al [27] have reported that the closed form of photochromic diarylethene derivatives bearing sulfone groups can fluoresce, which inspired our research.…”
mentioning
confidence: 85%
“…The photocyclization quantum yields F o-c of PMInDTEs were measured according to the literature method 24,25 (Supplementary Note 1 and Supplementary Table 4): proportion of parallel and anti-parallel conformation 19 . Therefore, the DTE in PMI-nDTEs system shows competitive ultraviolet sensitivity and contributes to the excellent fluorescence photoswitching performance.…”
Section: Resultsmentioning
confidence: 99%
“…FLIM) and various modes for achieving spatial super-resolution. The latter effort has also involved the generation of suitable organic and nanoparticular probes [19,20].…”
Section: Discussionmentioning
confidence: 99%